STATUS TANAH–TANAH KESULTANAN TERNATE DALAM PERSPEKTIF TANAH NASIONAL - Masyhud Asyhari (Fakultas Hukum Universitas Gadjah Mada, 2008)
Dispute on kingdom’s land (tanah swapraja) or ex-kingdom’s land emerged signi.cantly after the reformation era, such as at Deli Serdang Regency, Cirebon Municipality, Yogyakarta and also at Ternate. At Ternate, there has not been found the references that analysing the dispute on Ternate Kingdom’s land. The objectives of this research are to find out land law system on the Kingdom of Ternate, and the solution had been done to solve land problem on the Ternate Kingdom after the enactment Act No. 5 Year 1960 (UUPA). The results indicate that Ternate Kingdom has it own system of land law. Furthermore, the way of solution have been done by Government to settle kingdom’s land are slightly different between Ternate Kingdom with the other Kingdoms arround Indonesia.